Developing a framework for arts in health programs targeting individuals with chronic pain: a mixed-methods study of practitioners. (August 2021) - Koebner, I.J.; Chatterjee, H.J.; Tancredi, D.J.; Witt, C.M.; Gosdin, M.; Rawal, R.; Weinberg, G.; Meyers, F.J.
Abstract: Objectives: Chronic pain is a leading cause of morbidity and disability across the world. Cultural engagement may be a valuable tool in addressing the social disconnection that often accompanies chronic pain. This study sought to develop a framework for arts in health programs targeting individuals with chronic pain. Study design: Sequential explanatory mixed-methods study. Methods: Web-based, cross-sectional survey sent to arts and cultural professionals to assess their experience with arts in health programming. Semi-structured interviews conducted with a sample of survey respondents to explore their perspectives on targeted arts in health programming for individuals with chronic pain. Results: Between October 2019 and January 2020, 208 surveys were completed by arts and cultural professionals. One hundred and twenty (58%) of the respondents indicated that they currently run an arts in health or museums in health program. Among these 120 respondents, 52 (43%) targeted older adults, 50 (42%) targeted individuals with mental health concerns, and 18 (15%) targeted individuals living with pain. Improving well-being (101 [84%]) and reducing social isolation (90 [75%]) were the most common intended program outcomes, while improving pain was the least common outcome (26 [22%]). Fifteen survey respondents were interviewed. Interviewees identified four interdependent themes regarding best practices for arts in health programs pertaining to (1) program content and structure, (2) program facilitation, (3) partnerships, and (4) programs for individuals with chronic pain. Conclusions: The cultural sector can support chronic pain prevention and treatment efforts through the development of specialized programs. This study provides a framework for developing arts in health programs that support individuals living with chronic pain.